Relationship between service quality, servicescape and outpatient satisfaction : A case of Kuching Specialist Hospital / Rowena Cliffton ... [et al.] - Cliffton, Rowena; Saar, Nandy Marlina; Iskandar, Siti Maheran (2014)
Outpatients' satisfaction with the healthcare services is of great concern to healthcare providers. It is one of the key factors that can affect their healthcare seeking behaviours. These include the service quality which consists of quality of personnel, process of clinical care and administrative procedure in hospital and the servicescape which consists of infrastructure. The aim of the study is to examine the relationship between service quality, servicescape and outpatient satisfaction of services offers, to identify which factor is the most influenced towards outpatients' satisfaction when they get treatment and to identify which item is the most satisfied by outpatients when they get treatment in Kuching Specialist Hospital (KCSH). Thus, the study utilized data collected from 200 respondents (outpatient) through questionnaire as research instrument which conducted in KCSH (private hospital). It was found that there is a strong relationship between service quality, servicescape, and outpatient satisfaction of services offers in KcSH. Besides, process of clinical care is the most influenced factor contributed to patient's satisfaction. The most satisfied item in each factor is from personnel quality factor through which the outpatients were satisfied to be treated with courtesy and respect by hospital administrative staffs. It is recommended for hospital to maintain and improve the performance of clinical care process and the performance of treating the patient with courtesy and respect. The KCSH is also recommended to strive in order to maintain the high standard in keeping outpatients satisfied with the services they offered.